Women of reproductive age's use of maternal healthcare services and associated factors in Liben district, East Borena zone, Oromia Regional State, Ethiopia - Desta, Mekonnen; Mengistu, Serawit; Arero, Godana (Frontiers in Global Women's Health, 2024)
Background One of the most important health interventions for reducing maternal morbidity and death is the use of maternal healthcare services. In Ethiopia, maternal healthcare services are not well utilized, particularly in rural pastoralist communities, despite their significance. Therefore, the purpose of this study was to evaluate the use of maternal healthcare services and the characteristics that are related to it in the East Borena zone. Techniques: In September 2020, a community-based cross-sectional survey was carried out in Liben with 416 randomly selected mothers. Mothers who had given birth within the 12 months before the study comprised the respondents. Questionnaires given by interviewers were used to gather the data. The data were transferred to SPSS version 20 for analysis after being entered into Epi-Info version 4.1 for coding. The Kolmogorov-Smirnov, Hosmer, and Lemeshow goodness of fit tests were employed, along with descriptive statistics. Additionally, multivariate and binary logistic regression analyses were carried out. 95% CI and the odd ratio were used to examine the relationship between the outcome and predictive variables. Results At least one prenatal visit was received by 60% of moms. Only 21.2% and 17.5% of women had given birth in a medical facility and made use of early postnatal care services. The use of antenatal care was strongly correlated with maternal education [AOR = 2.43 (95% CI: 1.22–4.89)], decision-making capability [AOR = 2.40 (95% CI: 1.3–23.3)], felt compassionate and respectful treatment [AOR = 0.30 (95% CI: 0.18–0.50)], and intended current pregnancy [AOR = 0.22 (95% CI: 0.12–0.37)]. Moms b/n ages 15–19 had a 3.7-fold higher probability of giving birth in a hospitals than moms b/n ages 35 and 49 [AOR = 1.74 (95% CI: 1.02–3.08)]. Mothers who lived far away were 1.02 times less likely to give birth at a hospital than those who could reach one within an hour (AOR = 1.74;95% CI: 1.02, 3.08). While recent use of antenatal care [AOR = 5.34 (95% CI: 1.96–8.65)], planned current pregnancy, and knowledge of using postnatal care were shown to be strongly correlated with danger indicators [AOR = 2.93 (95% CI: 1.59–5.41)], knowledge of danger signs [AOR = 3.77 (95% CI: 2.16–6.57)] and perceived compassionate and respectful care were significantly associated with institutional delivery. Conclusion Overall the prevalence of maternal healthcare services utilization was far below the national and regional targets in the study area. Thus, promoting institutional services, raising community knowledge, empowering women to make decisions, and enhancing the infrastructure of the health sector.